Association of Slowly Expanding Lesions on MRI With Disability in People With Secondary Progressive Multiple Sclerosis. (26th April 2022) - Calvi, Alberto; Carrasco, Ferran Prados; Tur, Carmen; Chard, Declan T.; Stutters, Jonathan; De Angelis, Floriana; John, Nevin; Williams, Thomas; Doshi, Anisha; Samson, Rebecca S.; MacManus, David; Gandini Wheeler-Kingshott, Claudia A.; et al.
Abstract : Background and Objective: To explore the relationship between slowly expanding lesions (SELs) on MRI and disability in secondary progressive multiple sclerosis (SPMS). Methods: We retrospectively studied 345 patients with SPMS enrolled in the MS-SMART trial. They underwent brain MRI at baseline and at 24 and 96 weeks. Definite SELs were defined as concentrically expanding T2 lesions, as assessed by nonlinear deformation of volumetric T1-weighted images. Associations of SEL volumes with other MRI metrics and disability were assessed through Pearson correlations and regression analyses. Results: Averaged across patients, 29% of T2 lesions were classified as being definite SELs. A greater volume of definite SELs correlated with a higher total baseline T2 lesion volume ( r = 0.55, p < 0.001) and percentage brain volume reduction ( r = −0.26, p < 0.001), a higher number of new persisting T1 black holes ( r = 0.19, p < 0.001), and, in a subset of 106 patients, with a greater reduction in magnetization transfer ratio (adjusted difference 0.52, p < 0.001). In regression analyses, a higher definite SEL volume was associated with increasing disability, as assessed by the Expanded Disability Status Scale (β = 0.23, p = 0.020), z scores of the Multiple Sclerosis Functional Composite (β = −0.47, p = 0.048), Timed 25-Foot Walk Test (β = −2.10, p = 0.001), and Paced Auditory Serial Addition Task (β = −0.27, p = 0.006), and increased risk of disability progression (odds ratio 1.92, p = 0.025). Discussion: Definite SELs represent almost one-third of T2 lesions in SPMS. They are associated with neurodegenerative MRI markers and related to clinical worsening, suggesting that they may contribute to disease progression and be a new target for therapeutic interventions.